REE patterns and trustworthiness of stable carbon isotopes of Salitre Formation, Irecê Basin (Neoproterozoic), São Francisco Craton - Redivo, Henrique V.; Mizusaki, Ana M.P.; Santana, Ana V.A. (Journal of South American earth sciences, 2019)
Neoproterozoic limestones have been subject to variations in their original isotopic ratios, which has led to studies to verify the reliability of isotopic data obtained in these rocks. A Brazilian example of Neoproterozoic carbonate succession is found in Irecê Basin (BA) (Salitre Formation, São Francisco Supergroup). The present research aims to evaluate the reliability of the δ13C, mainly through REE patterns of samples gathered in Upper Nova America Unit. This unit represents an intermediate section included in a thick carbonate cover that represents the Salitre Formation. X-Ray fluorescence and inductive plasma mass spectrometry (ICP-MS) techniques were used to obtain elemental geochemistry. X-ray diffraction, including the fraction < 4 μm, and microscope with coupled fluorescence were used to verify the presence of carbonate, organic matter, siliciclastic phases and their proportions. Samples are mainly calcitic and have REE patterns with enrichment of light REEs, strong positive La anomalies, slightly positive Ce anomalies, variety of Gd anomalies, absence of strong Y anomaly and Y/Ho ratio of 31.5 ± 1.5. These anomalies indicate a mixture of oceanic and fresh waters during precipitation. Ce positive anomalies indicate anoxic states of early digenetic conditions of the environment. δ13C values have little contrast around 0‰. As a result, calcareous from Nova América Unit precipitated under shallow depths on carbonate platform. High concentration of Zr and SiO2 suggests high rates of weathering on marginal belts of São Francisco craton through high energy input of detrital material by freshwater. On the other hand, low concentration of Al2O3 indicates deposition of clay minerals occurred in a mild area of the plataform. The Mn/Sr and Fe/Sr ratios did not indicate the presence of significant diagenetic or metamorphic alterations. From the petrographic point of view, the samples do not present preserved organic matter, but they are recrystallized instead, sometimes dolomitized and dissolution features are present. The results indicate that Nova América limestones were precipitated on shallow carbonate restricted platform close to the coastline prone to fresh water and detrital input, therefore, δ13C does not correspond to the isotopic composition of the global ocean. •Reliability of δ13C of limestones of the Salitre Formation was studied.•Salitre Formation occurs in Irecê Basin (Neoproteroizoc), São Francisco Supergroup.•Pre-, syn- and post-depositional parameters and inedit REE patterns are discussed.•Fresh water and continental inputs affects chemical precipitation of the limestones.•The rocks precipitate near the coastline with intermediate rates of evaporation.